Ticks on passerines from the Archipelago of the Azores as hosts of borreliae and rickettsiae - Literak, I. (2019)
We examined the presence of borreliae and rickettsiae bacteria in ticks from wild passerine birds on three islands of the Archipelago of the Azores, the westernmost region of Palearctic. A total of 266 birds belonging to eight species from seven families were examined on São Miguel, Santa Maria and Graciosa islands in 2013. Ticks collected from these birds consisted of 55 Ixodes frontalis (22 larvae, 32 nymphs, 1 adult female) and 16 Haemaphysalis punctata nymphs. Turdus merula and Erithacus rubecula were the birds most infested with both tick species. Three T. merula in Santa Maria were infested with 4 I. frontalis infected with Borrelia turdi. No rickettsiae were found in the ticks.We reportfor the firsttime the presence of I. frontalis and B. turdi on the Azores islands and we showed that the spatial distribution reaches further west than previously thought.